“Respuesta del cultivo de maíz amarillo suave (zea mays var. Amilácea) a la aplicación de 4 dosis de roca fosfórica complementada con humus en el fundo aucaloma- Lamas” - Tananta Pinchi, Audrith (2014)
The present investigation work was carried out in the 1 Found Aucaloma • you Lick, county of San Martin, property of the National "University of San Martin", geographically characterized to present the following coordinates: Longitude west 76º42' and 06º16' of south latitude and 720 m. s. n. m. m., with the objective of evaluating the answer to the application of 4 dose of phosphoric rock supplemented with worm humus, the yield with characteristic agronomic appropriate, and to carry out the economic analysis of the best treatments. lt was evatuated the yield and the complementary vegetative characteristics using the statistical design of Blocks Totally at random (DBCA), with 6 treatments and 4 repetitions whose resutts were analyzed by means of the variance analysis and the test of multiple significance of Duncan. The sidebar distancing was of 0,80 cm, between arrays and 0,60 cm, among plants, the security you hyson with phosphoric rock, using the dose 800 kg/ha (80 kg/ha of P20s and 248 kg/ha of CaO), apptying that of nitrogen together with the match and potassium days after the sidebar and the one of remaining nitrogen a days after the sidebar and receiving a total precipitation during the period of investigation of 133.92 mm, with a maximum temperatura of 28.88 ºC. Of the results obtained according to the statisticat anatysis, you concludes; highty significant statistical difference exists with the treatments whose yietds T4 fluctuates among 3903,9 kg/ha of the treatment that corresponds the biggest yield respectively. According to characteristic agronomic evaluated and to the relationship benefice/cost, it was determinad to the variety amilácea, as promissory of good yietd potential and economically profitable, with net utilities that overcome the new suns, for each hectare of production. Keywords: phosphoric rock, nitrogen, match, variety amilácea.